Pengaruh Pemberian Kompos Kiambang dan Pupuk Majemuk pada Pertumbuhan Bibit Kakao (Theobroma cacao L.) - Iyan Indrawan; Any Kusumastuti; Bambang Utoyo (Jurnal Agro Industri Perkebunan, 2015)
The objective of this research is to measure the effect of giant salvinia compost and compound fertilizers on growth of cocoa seedlings. This research has been conducted in State Polytechnic of Lampung experimental garden, Rajabasa, Bandar Lampung on December 2014 until May 2015. The method used was a randomized block design (RBD). The factorial pattern consisting of two factors. The first factor was the rate of giant salvinia compost consists of four levels, namely: K0 = 0 g.polybag-1, K1 = 200 g.polybag-1, K2 = 300 g.polybag-1, and K3 = 400 g.polybag-1. The second factor was the rate of compound fertilizer consists of two levels, namely: M0 = 0 g.polybag-1, M1 = 5 g.polybag-1, M2 = 10 g.polybag-1. Data were analyzed by analysis of variance further significantly different if followed by LSD test at the 5% level of accuracy. Observations included plant height, number of leaves, stem diameter, root length, dry weight, and ratio of root-shoot dry weight. The results showed that giant salvinia affected on plant height, number of leaves, stem diameter, root length, and the ratio of root-shoot dry weight. Compound fertilizer also affected on plant height and number of leaves, stem diameter, root length, and and ratio of root-shoot dry weight. There was an interaction between rate of giant salvinia compost and compound fertilizer on length root.Keywords: compound fertilizer, giant salvinia compost, Theobroma cacao L.Permalink:Â http://jurnal.polinela.ac.id/index.php/AIP/article/view/18